The effects of an online learning environment with worked examples and peer feedback on students' argumentative essay writing and domain-specific knowledge acquisition in the field of biotechnology - Valero Haro, Anahuac; Noroozi, Omid; Biemans, Harm J.A.; Mulder, Martin (Journal of biological education, 2019)
The present study investigated the effects of an online learning environment supported with worked examples and peer feedback on students' argumentative essay writing and domain-specific knowledge acquisition in the field of biotechnology. As part of a bigger project, a pre- and post-test study design was used with 45 bachelor students who were randomly grouped in pairs. Students were asked to analyse a case and write an argumentative essay taking into account the advantages and disadvantages of genetically modified organisms. The results showed that the combination of worked examples and peer feedback improve the quality of argumentative essay writing and facilitate the acquisition of domain-specific knowledge. Implications, suggestions, and future research are discussed.